2021
DOI: 10.5194/cp-2021-155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A multi-ice-core, annual-layer-counted Greenland ice-core chronology for the last 3800 years: GICC21

Abstract: Abstract. Ice-core timescales are vital for the understanding of past climate; hence they should be updated whenever significant amounts of new data can contribute to improvements. Here, the Greenland ice-core chronology was revised for the last 3835 years by synchronizing six deep ice-cores and three shallow ice-cores from the central Greenland ice sheet. A layer-counting bias was found in all ice cores because of site-specific signal disturbances, and a manual comparison of all ice cores was deemed necessary… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The list of NH volcanism contains only volcanic deposits larger than 20 kg km −2 in any of the applied Greenland ice cores, and the list containing the Southern Hemi-sphere includes all deposition events larger than 10 kg km −2 for the Antarctic ice cores, which biases our list to larger eruptions. This cutoff is necessary because of the highly variable sulfate background in the Greenland cold periods of the last glacial predominantly associated with mineral dust (e.g., gypsum; Svensson et al, 2000) (Table S2). A sulfate deposition of 20 kg km −2 corresponds to half the Greenland deposition from the 1815 CE Tambora eruption (Sigl et al, 2015), and thus only quite large events in terms of total sulfur injections into the atmosphere are detected in this work.…”
Section: Volcanic Sulfate Deposition Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…The list of NH volcanism contains only volcanic deposits larger than 20 kg km −2 in any of the applied Greenland ice cores, and the list containing the Southern Hemi-sphere includes all deposition events larger than 10 kg km −2 for the Antarctic ice cores, which biases our list to larger eruptions. This cutoff is necessary because of the highly variable sulfate background in the Greenland cold periods of the last glacial predominantly associated with mineral dust (e.g., gypsum; Svensson et al, 2000) (Table S2). A sulfate deposition of 20 kg km −2 corresponds to half the Greenland deposition from the 1815 CE Tambora eruption (Sigl et al, 2015), and thus only quite large events in terms of total sulfur injections into the atmosphere are detected in this work.…”
Section: Volcanic Sulfate Deposition Recordsmentioning
confidence: 99%
“…2007; Robock, 2000). Large volcanic eruptions injecting sulfuric gases into the stratosphere and forming sulfate aerosols have a global or hemispheric cooling effect of several degrees lasting for several years after the eruption (Sigl et al, 2015;Sinnl et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The high temporal resolution in turn can enable the generation of annual-layer counted age models from the aerosol records (e.g. Sinnl et al, 2021). Aerosol records of both shallow and deep ice cores are routinely measured at high depth resolution using continuous melting and analysis setups, i.e., using so-called continuous flow analysis (CFA) (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We also provide a discussion of the uncertainties related to these changes covering analytical precision, depth-assignment and resolution. This paper accompanies the publication of the revision of the Greenland ice core chronology (GICC21) presented in Sinnl et al (2021), that makes extensive use of the data sets shown and discussed here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation